PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL PADA PENINGKATAN INDEKS PEMBANGUNAN MANUSIA - Candra Yunita Sari, Ida Ayu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2016)
Regional autonomy and fiscal decentralization enacted to give local governments the authority to increase local revenue and allocative function in local development priorities. This study purpose to determine effect of PAD and Capital Expenditure on Improving Human Development Index/HDI (Study at Regency/City in Bali). This study was conducted in 9 Regency/cities in Bali. This study uses budget realizationreport from 2009-2013 and HDI data 2008-2013. This research has been qualified classical assumption and test feasibility of model, processed by regression analysis techniques.Based on hypothesis test showed PAD and Capital Expenditure positive and significant impact on Improvement of HDI. Positive and significant effect of this means increased revenues and capital expenditures, will be increase HDI also. This increase is due to the allocation of Local Revenue and Capital Expenditure has been utilized appropriately so that planned activities can be well.
Keywords: local revenue, capital expenditure, human development index